Research opportunities for supplier selection: An analysis from literature reviews (2019)
This article aims to identify different literature reviews of supplier selection to analyze the topics addressed in these documents, and suggest research opportunities for future literature reviews in issues that have not been addressed in the literature or require a deeper approach. This study states that the majority of existing literature reviews focus on the analysis of supplier selection methods and criteria, and uncertainty management, environmental management, and sustainability have been addressed in recent years. As a conclusion, it is suggested to focus future literature reviews on topics such as risk management, statistical methods, methods applied to industry sectors, implementation of supplier selection to small and medium enterprises, comparative analysis of solution methods performance, and the adaptation of solution methods from areas different to supplier selection. Likewise, it is recommended to continue updating literature reviews related to green and sustainable supplier selection, and uncertainty management in supplier selection, especially for the last 3-5 years. Copyright © 2019. Jose Alejandro CANO and Carlos Javier AYALA.